Ask Question
3 February, 12:14

If x = 1 is a common root of ax² + ax + 2 = 0 and x² + x + b = 0, then ab =

0
Answers (1)
  1. 3 February, 13:17
    0
    ab = 2

    Step-by-step explanation:

    Given equations

    ax² + ax + 2 = 0

    x² + x + b = 0

    root of both the equation

    x = 1

    then we can plug in x = 1 in both the equation

    ax² + ax + 2 = 0 x² + x + b = 0

    a*1² + a*1 + 2 = 0 1² + 1 + b = 0

    a + a + 2 = 0 1 + 1 + b = 0

    2a + 2 = 0 2 + b = 0

    2a = - 2 b = - 2

    a = - 2/2 = - 1

    Thus,

    a = - 1

    b = - 2

    a*b = - 1*-2 = 2

    ab = 2
Know the Answer?